Colorimetric and fastness studies and analysis by reversed-phase high-performance liquid chromatography with diode-array detection of the dyeing of silk fabric with natural dye Helichrysum arenarium - (:unkn) unknown (WILEY, 2015)
In this study, silk fabric samples were dyed by various procedures using Helichrysum arenarium extracts. Alum, ferrous sulfate, stanium chloride, calcium nitrate, and potassium bitartrate were used as mordants. Reversed-phase high-performance liquid chromatography with diode-array detection was utilised for identification of the dyes present in the dyed silk fabrics and the plant extracts. The extraction of dyes was carried out with a hydrochloric acid/methanol/water (2:1:1 v/v/v) mixture. The colour coordinates and K/S values, as well as wash, light, and rub fastness, were determined.
Keywords: COTTON; IDENTIFICATION; HPLC